Synthesis, characterization and sensing application of HNTs@Pd-MoS2 ternary composite. (June 2022) - Turunc, Ersan
Abstract: In the current study, halloysite nanotube@palladium-molybdenum disulfide ternary composite (HNTs@Pd-MoS2 ) was synthesized. The characterization of HNTs@Pd-MoS2 ternary composite were carried out by Scanning electron microscopy (SEM), Energy-dispersive X-ray spectroscopy (EDX), Transmission electron micrsocopy (TEM), Fourier transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD) analysis and X-ray photoelectron spectroscopy (XPS). The as-synthesized HNTs@Pd-MoS2 ternary composite was utilized to prepare a sensor for electrochemical determination of dopamine. For this purpose, glassy carbon electrode (GCE) was modified with HNTs@Pd-MoS2 composite (HNTs@Pd-MoS2 /GCE), and the modified electrode was utilized for electrochemical determination of dopamine in phosphate buffer solutions. Under optimal conditions, the improved electrosensor demonstrated considerable response toward electrocatalytic oxidation of dopamine with tip a well linearity in the concentration range of 25–1000 μM. The detection limit (LOD) of the recommended electrosensor was forecasted to be 0.15 μM. The effectiveness of the proposed electrosensor was tested against some interferant substances such as uric acid, glucose, ascorbic acid and acetaminophen. The results showed that the proposed electrosensor does not have a significant current response to such interference materials. Furthermore, HNTs@Pd-MoS2 /GCE demonstrated a considerable reproducibility and fast-response time. As a result, it can be proffered that the modified GCE can be evaluated as an electrochemical sensor for determination of dopamine. Graphical Abstract: ga1